Evaluation of the diabetogenic effect of methotrexate in psoriatic arthritis patients with metabolic syndrome: a pilot study - Tannaz Dehpouri; Ghasem Rahmatpour Rokni; Nematollah Ahangar Narenjbon; Mohamad Goldust; Paul S. Yamauchi; Uwe Wollina; Torello Lotti; Leon Kircik; Vito Giuseppe Di Lernia; Sidharth Sonthalia; Alexandra Vojvodic; Jacek Szepietowski; et al. (PAGEPress Publications, 2019)
Methotrexate is a systemic immunosuppressant drug that is used for the treatment of psoriasis and psoriatic arthritis. Previous studies demonstrated a potential association between psoriasis and diabetes mellitus, obesity, atherosclerosis and hypertension. This study aimed at exploring the possible hyperglycaemic effects of methotrexate in psoriatic arthritis (PsA) patients. In this prospective cross-sectional study, 27 patients with PsA were evaluated. The status of PsA and presence of accompanying metabolic syndrome was determined by standard criteria and indexes. Blood indicators including, HbA1c, erythrocyte sedimentation rate, fasting blood sugar, total cholesterol, high-density lipoprotein, triglycerides, and C-reactive protein were examined before and 12 weeks after methotrexate therapy. There were no significant changes between HbA1c levels before and after methotrexate therapy in both genders (men: P=0.131, women: P=0.803). In addition, HbA1c levels in PsA patients with metabolic syndrome were not different before and after treatment (P=0.250). Finally, HbA1c levels did not change in PsA patients without metabolic syndrome before and after therapy (P=0.506). Methotrexate in PsA patients does not appear to have hyperglycaemic effects in the short-term and can be safely used in patients with metabolic syndrome and diabetes.